Making a Mathematical Model of Assembled Mill with Inserted Knives with Diffusion Fastening of Hard-Alloy Plates - Dubrovets Lyudmila Vladimirovna; Isamov Raim Nasimovich; Nematov Abror Akbar ugli (International Journal on Human-Computing Studies, 2021)
In this article, analysis of mathematical model of designs of the cutting tool of assembled mill with inserted knives with diffusion fastening of hard-alloy plates is given.